70-kDa Heat Shock Protein Downregulates Dynamin in Experimental Stroke: A New Therapeutic Target?. Issue 8 (August 2016) - Kim, Jong Youl; Kim, Nuri; Zheng, Zhen; Lee, Jong Eun; Yenari, Midori A.
Abstract : Background and Purpose—: The 70-kDa heat shock protein (Hsp70) protects brain cells in models of cerebral ischemia. Proteomic screening of mice subjected to middle cerebral artery occlusion identified dynamin as a major downregulated protein in Hsp70-overexpressing mice (Hsp70 transgenic mice). Dynamin-1 is expressed in neurons and participates in neurotransmission, but also transports the death receptor Fas to the cell surface, where it can be bound by its ligand and lead to apoptosis. Methods—: Mice were subjected to distal middle cerebral artery occlusion. Neuro-2a cells were subjected to oxygen glucose deprivation. Hsp70 transgenic and Hsp70-deficient (Hsp70 knockout) mice were compared with wild-type mice for histological and behavioral outcomes. Some mice and neuro-2a cell cultures were given dynasore, a dynamin inhibitor. Results—: Hsp70 transgenic mice had better outcomes, whereas Hsp70 knockout mice had worse outcomes compared with wild-type mice. This correlated with decreased and increased dynamin expression, respectively. Dynamin colocalized to neurons and Fas, with higher Fas levels and increased caspase-8 expression. Hsp70 induction in neuro-2a cells was protected from oxygen glucose deprivation, while downregulating dynamin and Fas expression. Further, dynamin inhibition was found to be neuroprotective. Conclusions—: Dynamin may facilitate Fas-mediated apoptotic death in the brain, and Hsp70 may protect by preventing this trafficking. Dynamin should be explored as a new therapeutic target for neuroprotection. Abstract : Supplemental Digital Content is available in the text.